Electrodeposition of aluminium from ionic liquids on high strength steel. (4th March 2019) - Böttcher, R.; Valitova, A.; Ispas, A.; Bund, A.
ABSTRACT: Electroplated aluminium from ionic liquids is a promising candidate for corrosion protection of steels due to its excellent corrosion resistance. The pretreatment of the substrate is a crucial step for good adhesion of the coating and hence its performance. Conventional aqueous pretreatment of the steel substrate prior to aluminium plating does not lead to satisfactory results. In this paper, the authors systematically investigated anodic polarisation of high strength steel in Lewis acidic 1-ethyl-3-methylimidazolium chloride/AlCl3 as an electrochemical pretreatment method. The study includes cyclic voltammetry, chronoamperometric and chronopotentiometric methods as well as SEM/EDS analysis, optical microscopy, completed by roughness measurements using laser scanning profilometry and AFM. The removal of oxides and impurities from the steel surface and an increase of the surface roughness leads to excellent adhesion of the deposits. In-situ anodic polarisation and subsequently deposition results in the formation of an aluminium-iron alloy. By separation of pretreatment and deposition baths, high quality pure aluminium deposits can be achieved. It is shown that the developed pretreatment process can be successfully applied for the coating of flat substrates as well as for fasteners; the latter in a barrel plating process. The coating shows good adhesion and is evenly distributed over the substrates. Furthermore, a method for removing ionic impurities ( e.g . iron) in the pre-treatment bath is suggested.